Coptica Palatina Koptische Texte aus der Heidelberger Papyrussammlung (P.Heid.Kopt.). Bearbeitet auf der Vierten Internationalen Sommerschule für Koptische Papyrologie Heidelberg, 26. August - 9. September 2012 - Boud'hors, Anne; Delattre, Alain; Schenke, Gesa; Richter, Tonio Sebastian; Schmelz, Georg (Studien und Texte aus der Heidelberger Papyrussamlung, 2019)
The texts compiled in Coptica Palatina were worked on by young scholars taking part in an International Summer School for Coptic Papyrology under the supervision of the editors. The volume offers editions of Coptic literary and magical texts, of private letters, as well as of legal and administrative documents, all complete with a commentary and a modern translation. These texts originate from different regions of Middle and Upper Egypt (Fayyum, Hermupolis, Bawit, Aphrodito, Esna, Apollonopolis magna) and are datable to the 6th/7th up to the 11th/12th centuries CE. The bulk of the material, however, comes from the 7th/8th century, the crucial period of Egypt's transition from a province of the Byzantine empire to a province of the early Islamic caliphate.